2012
DOI: 10.1007/s10967-012-1995-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on 226Ra, 232Th, 40K and 137Cs activity concentrations in vegetables and fruits frequently consumed by inhabitants of Elazığ Region, Turkey

Abstract: Determining radioactivity levels in foodstuffs is of great importance for the protection of human health. In addition, the literature includes few studies related to this subject in Turkey. In this study, gamma spectroscopic system was used in order to measure 226Ra, 232Th, 40K and 137Cs activity concentrations in vegetables and fruits produced in Elazığ Region. The average activity concentrations in vegetables was calculated as 0.64 ± 0.26 Bq kg−1 for 226Ra, 0.65 ± 0.14 Bq kg−1 for 232Th, 13.98 ± 1.22 Bq kg−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…Under natural environmental conditions, 137 Cs and 90 Sr mainly enter the human body through the food chain and respiration. Both 90 Sr and 137 Cs have long biological half-lives in the human body 3 8 , therefore it is important to continuously monitor 90 Sr and 137 Cs in environmental and food samples, especially those from the surroundings of nuclear facilities, to ensure the radiological safety of individuals and the environment. In contrast to 137 Cs, long-term monitoring data for 90 Sr activity in environmental and food samples worldwide are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural environmental conditions, 137 Cs and 90 Sr mainly enter the human body through the food chain and respiration. Both 90 Sr and 137 Cs have long biological half-lives in the human body 3 8 , therefore it is important to continuously monitor 90 Sr and 137 Cs in environmental and food samples, especially those from the surroundings of nuclear facilities, to ensure the radiological safety of individuals and the environment. In contrast to 137 Cs, long-term monitoring data for 90 Sr activity in environmental and food samples worldwide are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 There are some studies wich found the levels of natural radioactivity in Vegetables and Fruits samples consumed in different counters in the world. [5][6][7][8][9][10][11][12][13] High level of NORM has already been found in Iraq soil, especially once war 2003. Plants are the first recipients of the radionuclides from soil.…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.14500/aro.10736 natural gamma radiation due to the terrestrial radionuclides of 226 Ra, 232 Th, and 40 K. It can be calculated using Equation (4) (Taiwo, et al, 2014 232 Th, and 40 K in foodstuffs and the consumption rate of food and water by human beings affect the annual ingestion dose rates (UNSCEAR, 2000). The annual ingestion dose for Koya inhabitants (E ING ) coming from the consumption of wheat was calculated using the following equation given by (Canbazoglu andDogru, 2013, Salih, 2018).…”
Section: External Hazard Indices (H Ex )mentioning
confidence: 99%